2011
DOI: 10.1089/bfm.2010.0083
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Breastfeeding: An Unusual Practice That Might Be the Reason for Future Development of Contralateral Breast Disease

Abstract: Mothers who practice unilateral breastfeeding are candidates for future development of different breast problems in the unsuckled/less suckled breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On the other hand, the care measures also provided attention to the non-functioning breast, as the puerperal hormonal situation is different and implies surveillance of the breast-nipple unit. 6 This was important since, in most puerperal women and even without any pathology, engorgement, blockage of the milk ducts and nipple pain are the most frequent reasons for EBF abandonment. EBF is an option generally rejected by women with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the care measures also provided attention to the non-functioning breast, as the puerperal hormonal situation is different and implies surveillance of the breast-nipple unit. 6 This was important since, in most puerperal women and even without any pathology, engorgement, blockage of the milk ducts and nipple pain are the most frequent reasons for EBF abandonment. EBF is an option generally rejected by women with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…(4,5) In addition to the immediate benefits, EBF offers long-term gains and reduces the risk of diseases, namely breast cancer. Several theories invoke lower risk, based on the reduction of breast oestrogens, excretion of fat-soluble carcinogens, (6) differentiation of breast tissue and reduction of the number of ovulations in the years of life. (7) A number of studies conducted with Afro-Americans that displayed low adherence to breastfeeding showed high breast cancer rates.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical colleagues from Saudi Arabia, Baslaim et al, 5 bring to our attention some interesting results of breastfeeding only on one breast. This phenomenon was first reported by the Chinese Tanka boat people in 1977.…”
mentioning
confidence: 99%
“…The complaints about the unsuckled breast include generalized pain or heaviness, a mass with or without pain, or a nipple charge. Baslaim et al 5 report various morbidities in the unsuckled breast and suggest that some of these problems could be prevented if the breast has been suckled. Let us hear from you, if you have made similar observations.…”
mentioning
confidence: 99%
“…These included children only feeding on one breast, usually due to having a portacath, PEG, stoma or wound on one side of their body and the child refusing to lie on that side. Unilateral breastfeeding is not unheard of, but the literature largely discusses this in relation to maternal factors such as unilateral mastectomy (Baslaim et al, 2011;Ko et al, 2013;Barco et al, 2015). This is notable as unilateral breastfeeding due to infant breast preference is a risk factor for early cessation of breastfeeding and may also be a risk factor for breast cancer in the unsuckled breast (Novrial et al, 2020).…”
Section: Difficulties Indirectly Related To the Child's Conditionmentioning
confidence: 99%